Desmoplastic Fibroma Recurrence Associated with Tuberous Sclerosis in a Young Patient - A. M. Espinoza-Coronado; J. P. Loyola-Rodríguez; J. H. Olvera-Delgado; J. O. García-Cortes; J. F. Reyes-Macías (Case Reports in Dentistry)
Case Report. A nine-year-old patient with a diagnosis of tuberous sclerosis (with no pathological record) that showed calcifications at the brain level. Besides, the case showed the Vogt triad (epilepsy, mental retardation, and sebaceous adenoma). The patient clinically showed a volume increase of hard consistency, without suppuration and no sessile that included the following teeth 73, 74, and 75. Cone beam computed tomography (CBCT) was obtained, and it displayed a delimited unilocular lesion. After surgical excision, the histopathological report was desmoplastic fibroma (DF). It was observed that the patient had an aggressive recurrence of DF at four months after surgery treatment. Due to these clinical findings, resective osseous surgery and curettage were carried out. It is uncommon to find these two pathologies together (DF and tuberous sclerosis). Since DF is a benign pathology but very invasive and destructive, it is necessary a constant follow-up examination due to a high recurrence frequency.